Tanay Tourist and Community Center - Calalo, Louie Beatriz P.; Rivera, David (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
Tanay names itself as the regional tourism haven of the Rizal province. Abundant with natural land and water-forms, rich in culture, and blessed with fertile agricultural land, this project responds to the gap between tourists, locals, and the governing agency in making the tourism industry more economically and socially beneficial to the locals, and more respectful with the environment. In a society increasingly urbanized, the call for rural areas and its lifestyle becomes stronger, and with the advancement of infrastructure in upland Tanay, making the area more accessible, tourism as a development strategy is used. The need for a satellite governing body and economic hub which the project responds to not only serves as a node between tourists and locals, it also creates a gateway in upland Tanay. Where the site is located.
Includes appendices
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Architecture and tourism; Tourist information centers -- Rizal -- Philippines